Clement’s New Clothes. The Destruction of Old S. Clemente in Rome, the Eleventh-Century Frescoes, and the Cult of (Anti)Pope Clement III - Lila Yawn (Reti Medievali Rivista, 2012)
In the early 1100s, the fifth-century church of S. Clemente in Rome was buried beneath an entirely new basilica.  Inspired by suggestions published by Tommaso di Carpegna Falconieri (1998) and Valentino Pace (2007), the present article considers the possibility that this radical intervention constituted an act of damnatio memoriae or, better, of deletio memoriae, an obliteration of memory prompted by the nascent cult of miracles associated with Pope Paschal II’s enemy and rival, (anti)pope Clement III.  Clement III (Wibert of Ravenna) died in 1100, not long after the execution of an extensive fresco cycle in the early Christian basilica celebrating the miracles and cult of the first-century pope and martyr St. Clement I of Rome.  Resonances between these images and the prodigia attributed to Clement III may have invited analogies between the two Clements, especially during the turbulent early years of Paschal II’s pontificate, when Paschal, alarmed by reports of his adversary’s miracles, had Clement III’s corpse exhumed and thrown into the Tiber.